2018
DOI: 10.1111/pedi.12805
|View full text |Cite|
|
Sign up to set email alerts
|

Dysglycemia among youth with type 1 diabetes and suboptimal glycemic control in The Flexible Lifestyle Empowering Change (FLEX) trial

Abstract: Objective: To examine the prevalence and correlates of non-severe hypoglycemia among adolescents with type 1 diabetes and suboptimal glycemic control, an understudied topic in this group. Methods: Seven days of blinded continuous glucose monitor data were analyzed in 233 adolescents at baseline of the Flexible Lifestyle Empowering Change trial (13-16 years, type 1 diabetes duration >1 year, and hemoglobin A1c [HbA1c] 8-13% [64-119 mmol]). Incidence of clinical hypoglycemia (54-69 mg/dL) and clinically serious … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 37 publications
0
4
0
1
Order By: Relevance
“…For example, effect modification analyses of the FLEX trial showed that the intervention effect was stronger among participants with high vs low baseline HbA 1c percentages at 12 months (effect, 0.69%; 95% CI, 0.07%-1.31%; P for interaction = 0.03) and for female vs male participants at the 18 months (difference, 0.62; 95% CI, 0.03-1.21; P for interaction = 0.04). 6 In settings where more complex heterogeneity in participant profiles reliably predicts differential response to the efficacy of treatment, the precision medicine approach offers particular promise and addresses certain limitations of traditional effect modification. 7 The precision medicine approach seeks to develop an individualized treatment rule (ITR), a mathematical function that gives recommendations for whether a participant should receive intervention or not.…”
Section: Jama Network Open | Statistics and Research Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, effect modification analyses of the FLEX trial showed that the intervention effect was stronger among participants with high vs low baseline HbA 1c percentages at 12 months (effect, 0.69%; 95% CI, 0.07%-1.31%; P for interaction = 0.03) and for female vs male participants at the 18 months (difference, 0.62; 95% CI, 0.03-1.21; P for interaction = 0.04). 6 In settings where more complex heterogeneity in participant profiles reliably predicts differential response to the efficacy of treatment, the precision medicine approach offers particular promise and addresses certain limitations of traditional effect modification. 7 The precision medicine approach seeks to develop an individualized treatment rule (ITR), a mathematical function that gives recommendations for whether a participant should receive intervention or not.…”
Section: Jama Network Open | Statistics and Research Methodsmentioning
confidence: 99%
“…Analysis of differential response observed in a completed trial may take the form of an effect modification analysis, in which the observed effect of an intervention is examined across levels of a third, prespecified effect modifier variable. For example, effect modification analyses of the FLEX trial showed that the intervention effect was stronger among participants with high vs low baseline HbA 1c percentages at 12 months (effect, 0.69%; 95% CI, 0.07%-1.31%; P for interaction = 0.03) and for female vs male participants at the 18 months (difference, 0.62; 95% CI, 0.03-1.21; P for interaction = 0.04) …”
Section: Introductionmentioning
confidence: 99%
“…The FLEX study is registered on clinicaltrials.gov, NCT01286350, and a detailed description of the design, 17 main results 18,38 and secondary analyses [39][40][41][42] of the FLEX study have been previously published.…”
Section: Protocolmentioning
confidence: 99%
“…Given that the Child and Adolescent Mindfulness Measure (CAMM) was only collected at the 12-and 18-month visits, the present analyses used only 18-month CGM data. Consistent with previous FLEX analyses, 39,40 participants were included in the present analysis if they had greater than 24 total hours of CGM data over the seven-day wear period. Of the 198 participants with CGM data at 18-months, 131 also had CAMM data at 18-months.…”
Section: Continuous Glucose Monitoring (Cgm)mentioning
confidence: 99%